Securities Transaction Assistance Based On Capital Market Trading Mechanism In Indonesia With Interactive Simulation In Kendari City - Rizki Satria; Dwinofeli Agustiawan; Masno Marjohan (Indonesian Development of Economics and Administration Journal, 2025)
. The capital market is vital for Indonesia's economy, providing mechanisms for companies to raise funds and for individuals to invest. However, in Kendari City, public participation in securities investment remains low, largely due to limited knowledge and accessibility. This study investigates the trading mechanisms of Indonesia's capital market, identifies challenges faced by the community in Kendari, and explores the use of interactive simulations as an innovative mentoring tool. A qualitative case study approach was employed, incorporating observations, interviews, and thematic analysis. Results demonstrate that interactive simulations effectively enhance understanding and confidence in securities transactions, leading to greater participation and better financial decision-making. The findings underscore the importance of financial education programs that integrate modern technological tools to improve public literacy and engagement in the capital market. Recommendations are provided for stakeholders to optimize these strategies for broader implementation, fostering sustainable growth in Kendari's capital market.